NILAI NILAI PENDIDIKAN AKHLAK DALAM AL-QURAN - Riki Adi Pratama; Wildayah Musyafa; Ainal Ghani; Guntur Cahaya Kesuma; A.Fatoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the values of moral education as reflected in the Qur’an, which serves as the primary source of Islamic teachings and ethical guidance. The research problem arises from the reality that contemporary moral decline among society, particularly among the younger generation, often indicates a weak internalization of Qur’anic values. The aim of this study is to identify, analyze, and describe the educational principles of akhlak contained in the Qur’an, as well as their relevance to current educational contexts. This research employs a qualitative descriptive method with a literature-based approach, collecting data from classical and contemporary tafsir works, scholarly articles, and relevant references. The analysis was conducted through content analysis, focusing on verses that emphasize moral values such as honesty, respect, responsibility, patience, and sincerity. The results show that Qur’anic verses provide a holistic framework for moral education, highlighting the integration between faith, worship, and social interaction. These findings suggest that moral education based on the Qur’an is not only normative but also practical, offering guidance for character formation, especially in facing the challenges of modern society. This study contributes to the reinforcement of Islamic education by promoting Qur’anic moral values as a solution to address ethical crises in today’s world.